Making Meetings Work : Achieving high quality group decisions - Tropman, John E. (Sage Publications, Inc., 2003)
A best-seller in its first edition, Making Meetings Work: Achieving High Quality Group Decisions, Second Edition covers everything you need to know about organizing engaging meetings, including preparing agendas, controlling what happens behind the scenes prior to and after meetings, and managing conflicting values and personalities. Through the Meeting Masters Research Project at the University of Michigan, author John E. Tropman observed and interviewed the nation's most successful meeting experts to find out how to make meetings both stimulating and productive. Based on his findings, Tropman formulated seven principles and fourteen commandments for implementing dynamic meetings.